Effect of Partial Replacement of Cement with Micro Silica on The Mechanical Properties of Concrete Before and After Exposure to Seawater (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Concrete structures in marine environments are vulnerable to chloride and sulphate attack, leading to corrosion and reduced mechanical performance. This study examines the effect of partially replacing cement with microsilica at 5 w%, 10 w%, and 15 w% on the compressive and tensile strengths of concrete before and after 28 days of seawater exposure. Concrete mixes were designed with a ratio of 1:2:4 and a water/cement ratio of 0.4. The inclusion of microsilica significantly enhanced compressive strength before exposure, with the optimum performance observed at 10 w% replacement, showing a 26.1% increase after seawater exposure. Conversely, tensile strength declined across all mixes following exposure, with reductions between 18.45% and 27.19%, attributed to the ingress of chloride and sulphate ions that weakened the interfacial transition zone. Despite this, microsilica-modified concretes retained higher residual tensile strength than the control mix. The findings indicate that microsilica improves the strength and durability of concrete exposed to marine environments, making it an effective supplementary cementitious material for sustainable coastal and offshore applications.